Characterization of five CHASE-containing histidine kinase receptors from Populus × canadensis cv. Robusta sensing isoprenoid and aromatic cytokinins - Jaworek, Pavel; Tarkowski, Petr; Hluska, Tomáš; Kouřil, Štěpán; Vrobel, Ondřej; Nisler, Jaroslav; Kopečný, David (Planta, 2019)
Five poplar CHASE-containing histidine kinase receptors bind cytokinins and display kinase activities. Both endogenous isoprenoid and aromatic cytokinins bind to the receptors in live cell assays. Cytokinins are phytohormones that play key roles in various developmental processes in plants. The poplar species Populus × canadensis, cv. Robusta, is the first organism found to contain aromatic cytokinins. Here, we report the functional characterization of five CHASE-containing histidine kinases from P. × canadensis: PcHK2, PcHK3a, PcHK3b, PcHK4a and PcHK4b. A qPCR analysis revealed high transcript levels of all PcHKs other than PcHK4b across multiple poplar organs. The ligand specificity was determined using a live cell Escherichia coli assay and we provide evidence based on UHPLC-MS/MS data that ribosides can be true ligands. PcHK2 exhibited higher sensitivity to iP-type cytokinins than the other receptors, while PcHK3a and PcHK3b bound these cytokinins much more weakly, because they possess two isoleucine residues that clash with the cytokinin base and destabilize its binding. All receptors display kinase activity but their activation ratios in the presence/absence of cytokinin differ significantly. PcHK4a displays over 400-fold higher kinase activity in the presence of cytokinin, suggesting involvement in strong responses to changes in cytokinin levels. trans-Zeatin was both the most abundant cytokinin in poplar and that with the highest variation in abundance, which is consistent with its strong binding to all five HKs and activation of cytokinin signaling via A-type response regulators. The aromatic cytokinins' biological significance remains unclear, their levels vary diurnally, seasonally, and annually. PcHK3 and PcHK4 display the strongest binding at pH 7.5 and 5.5, respectively, in line with their putative membrane localization in the endoplasmic reticulum and plasma membrane.
Keywords: Cytokinins; Isoprenoid cytokinin; Populus; Terpenes; Topolin; tandemová hmotnostní spektrometrie; histidinkinasa; Aromatic cytokinin; terpeny; Poplar; Hormone; Histidine Kinase; Histidine kinase; cytokininy; Tandem Mass Spectrometry